Reconstruction of internal structures of Nilaparvata lugens using micro-computer tomography technology (Micro CT) - SHU Runguo; ZHOU Hang; CAO Zixiong; HE Kang; LI Fei (浙江大学学报. 农业与生命科学版)
The brown planthopper (Nilaparvata lugens) is an important rice pest. In this study, the tomographic images of adult brown planthopper were obtained by using micro-computer tomography technology (Micro CT). Three-dimensional models of internal tissues and organs of the brown planthopper were established by combining manual modeling and deep learning. Three-dimensional models of the central nervous system, muscle tissue, alimentary canal and reproductive system of the brown planthopper were obtained. These models preserved the original morphologies of these structures and accurately restored the spatial arrangement of all tissues and organs within the brown planthopper. Measurements of the internal organization of insects were analyzed using Dragonfly software. This study established and refined the three-dimensional reconstruction technique of insect tissues and organs, which can contribute to a more precise view of the internal organization structure of insects and can be used for phenotypic observation of insect morphology and organ development. It provides a new technique for insect development investigation and gene function analysis in entomology.